1988
DOI: 10.2105/ajph.78.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic giardiasis caused by a contaminated public water supply.

Abstract: In the period November 1, 1985 to January 31, 1986, 703 cases of giardiasis were reported in Pittsfield, Massachusetts (population 50,265). The community obtained its water from two main reservoirs (A and B) and an auxiliary reservoir (C). Potable water was chlorinated but not filtered. The incidence of illness peaked approximately two weeks after the city began obtaining a major portion of its water from reservoir C, which had not been used for three years. The attack rate of giardiasis for residents of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 10 publications
2
31
0
2
Order By: Relevance
“…Giardiasis was most prevalent in children with poor water supplies, principally those lacking piped water, although it is known that Giardia survives in chlorinated water 14 . To protect against transmission, all drinking water should receive chemical pretreatment, preferably with sedimentation and filtration in addition to disinfection 25 , and municipal water should be supplied with a concentration of less than 0.7 to 70 cysts per 100 liters 40 ; however in the department of Antioquia, this level of control is not achieved. Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Giardiasis was most prevalent in children with poor water supplies, principally those lacking piped water, although it is known that Giardia survives in chlorinated water 14 . To protect against transmission, all drinking water should receive chemical pretreatment, preferably with sedimentation and filtration in addition to disinfection 25 , and municipal water should be supplied with a concentration of less than 0.7 to 70 cysts per 100 liters 40 ; however in the department of Antioquia, this level of control is not achieved. Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Humans represent the main reservoir for giardiasis (American Public Health Association 2000). During giardiasis epidemics associated with water consumption, beavers were also identified as a probable or suspected parasitic reservoir in Canada (Moorehead et al 1990;Isaac-Renton & Philion 1992) and the United States (Dykes et al 1980;Kent et al 1988). However, the status of giardiasis as a zoonosis remains a matter of debate (Vesy & Peterson 1999).…”
Section: Risk Of Giardiasis Associated With Water Supply In An Endemimentioning
confidence: 99%
“…Findings have shown that the consumption of either untreated, inadequately treated or simply chlorinated water has been the source of a number of giardiasis epidemics (Kent et al 1988;Ljungstrom & Castor 1992;Isaac-Renton et al 1994). In Quebec, where the disease is essentially endemic, approximately 14% of the population in a municipal distribution system is supplied with surface or well water at risk of contamination and treated by chlorination only.…”
Section: Introductionmentioning
confidence: 99%
“…22 Disease outbreaks related to the contamination of water supplies by G. lamblia have been reported in several regions of the United States. [23][24][25] Kent et al found that animal fecal waste in areas surrounding one reservoir tested high for Giardia cysts and concluded that contaminated fecal waste in close proximity to a major water supply could have been the cause of an outbreak of giardiasis. 24 Outbreaks of giardiasis have also resulted from flooding, heavy water runoff due to warm weather, and seasonal changes leading to the melting of ice and snow.…”
Section: Effects Of Hurricane Floydmentioning
confidence: 99%